Disponibilidade, demanda hídrica e problemáticas socioambientais: arquipélago de Fernando de Noronha/PE - Gouveia, Mariano Araújo Caccia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Fernando de Noronha, oceanic island of 17 square kilometers, located in the archipelago of the same name which is 545 km far from Recife, the capital of Pernambuco state, has a local population of about 4,000 inhabitants. However, this population is increased by an average of 60,000 people a year who visit the island because of the strength of its natural landscapes as a tourism product. The significant population increase, in an area of limited availability of water resources, leads to serious problems of environmental order, implying even the degradation of those who are its main attributes: its natural landscapes. Seeking to evaluate the extent of such conflict between use and availability of water resources, water quality and public water supply service, effluents production and treatment processes, as well as the public policies adopted to minimize these problems, we present this work developed from data collection during the second semester of 2013, as well as analysis of documents acquired through the institutions: administration of the archipelago, Pernambuco sanitation company (COMPESA), Chico Mendes institute for biodiversity conservation (ICMBio), brazilian institute of geography and statistics (IBGE) among others. The results also show up data to evaluate the potential capacity of rainwater harvesting as a possibility to supply the demand of water resources not satisfactorily attended by existing systems on the island

Fernando de Noronha, ilha oceânica de 17 Km², localizada no arquipélago de mesmo nome a 545 km de Recife, capital do estado de Pernambuco, apresenta uma população local de aproximadamente 4.000 habitantes. Entretanto, essa população é acrescida em média de 60.000 pessoas ao ano, que visitam a ilha graças à força de suas paisagens naturais como produto turístico. O expressivo aporte populacional, em área de limitada disponibilidade de recursos hídricos, acarreta sérios problemas de ordem socioambiental, implicando até mesmo na degradação daqueles que são seus principais atributos: suas paisagens naturais. Buscando avaliar a dimensão desse conflito entre uso e disponibilidade de recursos hídricos, qualidade da água e do serviço de abastecimento público, produção e processos de tratamento dos efluentes líquidos, bem como as políticas públicas adotadas para minimizar esses problemas, apresenta-se este trabalho desenvolvido a partir da coleta de dados em campo, durante o segundo semestre de 2013, além da análise de documentos adquiridos através das instituições: Administração do Arquipélago, Companhia Pernambucana de Saneamento (COMPESA), Instituto Chico Mendes de Conservação da Biodiversidade (ICMBio), Instituto Brasileiro de Geografia e Estatística (IBGE) entre outras. Como resultados apresentam-se também dados relativos à avaliação da capacidade potencial de captação de águas pluviais, como possibilidade de atendimento à demanda de recursos hídricos não atendida satisfatoriamente pelos sistemas existentes na ilha
Keywords: Abastecimento de água; Água - Captação; Oferta e procura; Políticas públicas; Fernando de Noronha, Arquipelago de (PE); Aguas residuais